Auditoría ambiental: responsabilidad de todos. - Ochoa, Verónica; Loor, Cindy; Ortega, Kyra (My University, 2015)
Today globalization has led to improved financial and monetary area, this has made to improve competitiveness indices organizations. Global changes proposed relevantly awareness of global environmental culture in order to contribute to a healthier planet. Proper management of environmental protection instruments, give opportunity for a new business ethics and corporate social responsibility, resulting in sustainable development and sustainable ecosystem, where organizations voluntarily decide to contribute to the achievement of a better society and a means cleaner environment. This process uses a resource awareness environmental audit, which proposes to discuss the appropriate parameters for contribution to the environment and the normal course of business activities, monitoring and evaluating compliance with environmental measures given by the respective agencies, in avoid an excessive pollution.
En la actualidad la globalización ha conllevado a mejorar el área financiera y monetaria, esto ha hecho que mejoren los índices de competitividad de las organizaciones. Los cambios globales proponen concienciar de forma relevante la cultura ambiental global con el objeto de contribuir al logro de un planeta más saludable. El manejo adecuado de los instrumentos de protección ambiental, darán oportunidad a una nueva ética empresarial y responsabilidad social corporativa, dando como resultado el desarrollo sostenible y sustentable del ecosistema, donde las organizaciones buscan contribuir en pro del medio ambiente. Este proceso de concientización utiliza como recurso la auditoría ambiental, la cual propone debatir los parámetros adecuados para la contribución al medio ambiente y el normal desarrollo de las actividades empresariales, evaluando el seguimiento y cumplimiento de las medidas ambientales impartidas por los organismos respectivos, con el fin de evitar una desmesurada contaminación ambiental.
Keywords: COMPETITIVIDAD; POLÍTICAS AMBIENTALES; RESPONSABILIDAD SOCIAL CORPORATIVA; DESARROLLO SOSTENIBLE